Pengaruh Pengeluaran Pemerintah dan Produk Domestik Regional Bruto (PDRB) Harga Berlaku Terhadap Pendapatan Asli Daerah (PAD) Di Sumatera Utara Periode 2010-2022 - Dwi Anggriani; Shabilla Aisyah; Wandira Anzani (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
The aim of this research is to examine how government spending and GDP affect North Sumatra's Original Regional Income (PAD) between 2010 and 2022. Multiple linear regression and the 95% significance threshold are two data analysis approaches used in the quantitative research approach. The findings of the simultaneous analysis show that GDP and government spending at current prices significantly and favorably affect North Sumatra's PAD. Government spending has a sizable and beneficial impact on North Sumatra's PAD, to a certain extent. Nevertheless, during 2010–2022, North Sumatra's PAD is positively influenced by current GDP in an insignificant way.